2022
DOI: 10.3389/fspor.2022.870692
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health in German Paralympic Athletes During the 1st Year of the COVID-19 Pandemic Compared to a General Population Sample

Abstract: IntroductionThe COVID-19 pandemic has huge influences on daily life and is not only associated with physical but also with major psychological impacts. Mental health problems and disorders are frequently present in elite paralympic athletes. Due to the pandemic situation, new stressors (e.g., loss of routine, financial insecurity) might act upon the athletes. Therefore, the assessment of mental health in athletes during the COVID-19 pandemic is important to identify prevalence of psychological problems and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 31 publications
2
26
1
Order By: Relevance
“…Half of the participants worried about their own well-being, 25% about their career, and only 8% had economical-financial preoccupations. Similar results were reported by the same author group in another investigation (Busch et al, 2022), where seventy-eight paralympic athletes (40 women, 38 men, mean age 29.8 ± 11.4 years) were recruited and matched against the general population (mean age 30.5 ± 10.9 years). The para-athletes reported significantly lower scores on the "Patient Health Questionnaire 4" (PHQ-4) scale at each measurement time point compared to the matched control group.…”
Section: Impact Of Covid-19-induced Confinement On Mental Health In P...supporting
confidence: 84%
See 1 more Smart Citation
“…Half of the participants worried about their own well-being, 25% about their career, and only 8% had economical-financial preoccupations. Similar results were reported by the same author group in another investigation (Busch et al, 2022), where seventy-eight paralympic athletes (40 women, 38 men, mean age 29.8 ± 11.4 years) were recruited and matched against the general population (mean age 30.5 ± 10.9 years). The para-athletes reported significantly lower scores on the "Patient Health Questionnaire 4" (PHQ-4) scale at each measurement time point compared to the matched control group.…”
Section: Impact Of Covid-19-induced Confinement On Mental Health In P...supporting
confidence: 84%
“…These populations have had to experience unique challenges during the COVID-19 pandemic, which has been "a tale of two stories": the infectious outbreak and disability. Living with disabilities, these populations are at higher risk for contracting the emerging coronavirus compared with the general population, besides facing psychological distress (Busch et al, 2022;Dehghansai et al, 2021;Hu et al, 2021;Kaneda et al, 2021), due to several, intersecting mediators (Jesus et al, 2020;Lund, 2020;Lund et al, 2020;Jesus et al, 2021a;Jesus et al, 2021b;Kamalakannan et al, 2021;Goddard et al, 2022), as mentioned before. Dehghansai et al (2021) performed a qualitative study interviewing seven Australian para-athletes, in order to capture the unique challenges of athletes with disabilities during the outbreak.…”
Section: Impact Of Covid-19-induced Confinement On Mental Health In P...mentioning
confidence: 94%
“…However, this study did not do separate analysis on Olympic and Paralympic athletes. Also a recent study from Germany assessed elite Para athletes' mental health during the pandemic, and it was demonstrated that lower PHQ-4 values were reported by the para-athletes compared to the general population ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…The PHQ-4 is a brief screening scale with four items in total for anxiety (e.g., “Feeling nervous, anxious or on the edge”) and depression (e.g., “Feeling down, depressed or hopeless”) ( 52 ). PHQ-4 has been used in other studies in sports medicine ( 30 , 53 , 54 ). The participants were asked to report how often they had been bothered with the following problems on this scale in the last week: 0 = Not at all; 1 = Several days; 2 = More than half the days; 3 = Nearly every day.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation